Effect of Low-Level Laser Therapy on The Number of Lymphocytes in Oral Ulcer Healing of Immunosuppressed Rats - Reiska Kumala Bakti; Desiana Radithia; Nurina Febriyanti Ayuningtyas; Fatma Yasmin Mahdani; Ghinaya Shaliha Nursaida Nisa (Denta: Jurnal Kedokteran Gigi, 2026)
Background: Glucocorticoid-induced immunosuppression disrupts cellular immune responses, including lymphocyte function, and delays oral traumatic ulcer healing. Low-Level Laser Therapy (LLLT) offers an alternative for healing traumatic oral ulcers in immunosuppressed patients. Objective: To analyze the effect of 650 nm LLLT on the number of lymphocytes in traumatic ulcer tissue of immunosuppressed Wistar rats. Materials and Methods: Experimental laboratory study with a randomized post-test-only control group design. Wistar rats were immunosuppressed with dexamethasone (7.2 mg/kg/day for 5 days), and traumatic ulcers were induced in the labial mucosa. Two groups were compared: a doxycycline-irrigated control group and a treatment group receiving doxycycline irrigation combined with 650 nm LLLT (50 mW for 1 minute). Animals were euthanized on days 2, 4, 6, and 8 (n=4). Lymphocytes, small cells with large, dark hyperchromatic nuclei, were counted in HE-stained histopathological sections of periulcer connective tissue at 400x magnification by oral pathologists. Results: Significant differences were observed between control and treatment groups (p